2021
DOI: 10.3390/magnetochemistry7100138
|View full text |Cite
|
Sign up to set email alerts
|

The Underexplored Field of Lanthanide Complexes with Helicene Ligands: Towards Chiral Lanthanide Single Molecule Magnets

Abstract: The effective combination of chirality and magnetism in a single crystalline material can lead to fascinating cross-effects, such as magneto–chiral dichroism. Among a large variety of chiral ligands utilized in the design and synthesis of chiral magnetic materials, helicenes seem to be the most appealing ones, due to the exceptionally high specific rotation values that reach thousands of deg×cm3×g−1×dm−1, which is two orders of magnitude higher than for compounds with chiral carbon atoms. Despite the sizeable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 73 publications
(85 reference statements)
0
6
0
Order By: Relevance
“…However, generating helicene‐based metal‐organic 1D polymeric architectures remains challenging and very few examples are described in the literature [35] . Recently, we have shown that 3‐(2‐pyridyl)‐4‐aza[6]‐helicene (H6bpy) bearing a 2,2′‐bipyridine coordinating unit can accommodate a lanthanide ion and combine the inherent properties of the helicenic ligand with those of the lanthanide to create unprecedented chiral SMMs ( 1 ) (Figure 1a), [36–39] efficient singlet oxygen sensitizers, [40] and strong MChD response in the NIR range of the electromagnetic spectrum [41–43] . Despite their pertinent chiroptical properties, chiral emissive Yb III complexes are still scarce [18, 19, 44–49] .…”
Section: Introductionmentioning
confidence: 99%
“…However, generating helicene‐based metal‐organic 1D polymeric architectures remains challenging and very few examples are described in the literature [35] . Recently, we have shown that 3‐(2‐pyridyl)‐4‐aza[6]‐helicene (H6bpy) bearing a 2,2′‐bipyridine coordinating unit can accommodate a lanthanide ion and combine the inherent properties of the helicenic ligand with those of the lanthanide to create unprecedented chiral SMMs ( 1 ) (Figure 1a), [36–39] efficient singlet oxygen sensitizers, [40] and strong MChD response in the NIR range of the electromagnetic spectrum [41–43] . Despite their pertinent chiroptical properties, chiral emissive Yb III complexes are still scarce [18, 19, 44–49] .…”
Section: Introductionmentioning
confidence: 99%
“… [35] Recently, we have shown that 3‐(2‐pyridyl)‐4‐aza[6]‐helicene (H6bpy) bearing a 2,2′‐bipyridine coordinating unit can accommodate a lanthanide ion and combine the inherent properties of the helicenic ligand with those of the lanthanide to create unprecedented chiral SMMs ( 1 ) (Figure 1a ),[ 36 , 37 , 38 , 39 ] efficient singlet oxygen sensitizers, [40] and strong MChD response in the NIR range of the electromagnetic spectrum. [ 41 , 42 , 43 ] Despite their pertinent chiroptical properties, chiral emissive Yb III complexes are still scarce. [ 18 , 19 , 44 , 45 , 46 , 47 , 48 , 49 ] Herein, we describe the synthesis of the first homochiral monodimensional coordination polymer (1D‐CP), namely M ‐ and P ‐[H6(py) 2 Yb(hfac) 3 ] n 2 and its structural features.…”
Section: Introductionmentioning
confidence: 99%
“…In 2021, [289] D. Pinkowicz et al. reviewed recent results on helicene‐ 4 f complexes in the framework of chiral lanthanide complexes, while in 2023 [280] the already mentioned review by S. Chorazy et al.…”
Section: First Steps In a New Research Field The Case Study Of 4 F‐smmmentioning
confidence: 99%